Structural Properties of CuFe2O4/ZnO Nanocomposite: Insights from X-ray Diffraction and Extended X-ray Absorption Fine Structure - Thanh Loan, To; Viet Nga, Tran Thi; Thanh, Nguyen Kim (VNU Journal of Science: Mathematics - Physics, 2024)
This work presents a comprehensive study of the structural properties of a CuFe 2 O 4 /ZnO nanocomposite, with a CuFe 2 O 4 /ZnO ratio of 1:1. CuFe 2 O 4 /ZnO nanocomposite was synthesized using a two-step co-precipitation method. First, CuFe 2 O 4 nanoparticles were prepared using the spray co-precipitation technique, then the nanoparticles were modified by sodium citrate and coated with ZnO. The structural parameters of both the crystal and local structures of the CuFe 2 O 4 constituent within the nanocomposite were obtained by using a combination of X-ray diffraction (XRD) and extended X-ray absorption fine structure (EXAFS) analyses. The obtained results indicated that both the crystal and local structures of the CuFe 2 O 4 constituent in the nanocomposite form are not affected by the ZnO coating. The CuFe 2 O 4 constituent has a cubic spinel structure with 15% of Cu 2+ ions distributed in the tetrahedral sites. Interatomic distances have been identified both as averages and specifically around Fe and Cu atoms to determine any sub-lattice distortion and the formation of distinct sub-lattices around Fe and Cu atoms in the cubic structure.